O pochodzeniu nazwy Polski - Mańczak, Witold (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
The text presents an opinion in the discussion on the etymology of the choronym Polska / Polonia. The author argues with Przemysław Urbańczyk, who claims that the name of Polons and Polonia has no connection with the tribe of Polans. On the contrary the opinion presented in the article maintains the historical truth according to which the Polans, whose name was mentioned, spread in the larger territory than the region inhabited originally by them. The author cites other similar examples in the history of tribes, nations and the formation of their denominative identity.